Detection and treatment of Fiebig stage I HIV-1 infection in young at-risk women in South Africa: a prospective cohort study. Issue 1 (January 2018) - Dong, Krista L; Moodley, Amber; Kwon, Douglas S; Ghebremichael, Musie S; Dong, Mary; Ismail, Nasreen; Ndhlovu, Zaza M; Mabuka, Jenniffer M; Muema, Daniel M; Pretorius, Karyn; Lin, Nina; Walker, Bruce D; et al.
Summary: Background: HIV incidence among young women in sub-Saharan Africa remains high and their inclusion in vaccine and cure efforts is crucial. We aimed to establish a cohort of young women detected during Fiebig stage I acute HIV infection in whom treatment was initiated immediately after diagnosis to advance research in this high-risk group. Methods: 945 women aged 18–23 years in KwaZulu-Natal, South Africa, who were HIV uninfected and sexually active consented to HIV-1 RNA testing twice a week and biological sampling and risk assessment every 3 months during participation in a 48–96 week life-skills and job-readiness programme. We analysed the effect of immediate combination antiretroviral therapy (ART) on viraemia and immune responses, sexual risk behaviour, and the effect of the socioeconomic intervention. Findings: 42 women were diagnosed with acute HIV infection between Dec 1, 2012, and June 30, 2016, (incidence 8·2 per 100 person-years, 95% CI 5·9–11·1), of whom 36 (86%) were diagnosed in Fiebig stage I infection with a median initial viral load of 2·97 log10 copies per mL (IQR 2·42–3·85). 23 of these 36 women started ART at a median of 1 day (1–1) after detection, which limited the median peak viral load to 4·22 log10 copies per mL (3·27–4·83) and the CD4 nadir to 685 cells per μL (561–802). ART also suppressed viral load (to <20 copies per mL) within a median of 16 days (12–26) and, in 20 (87%) of 23 women, prevented seroconversion, as shown with western blotting. 385 women completed the 48 week socioeconomic intervention, of whom 231 were followed up for 1 year. 202 (87%) of these 231 women were placed in jobs, returned to school, or started a business. Interpretation: Frequent HIV screening combined with a socioeconomic intervention facilitated sampling and risk assessment before and after infection. In addition to detection of acute infection and immediate treatment, we established a cohort optimised for prevention and cure research. Funding: Bill & Melinda Gates Foundation, National Institute of Allergy and Infectious Diseases, International AIDS Vaccine Initiative, Wellcome Trust, Howard Hughes Medical Institute.